Czym jest dziś czytanie literatury? Ankieta - Brzozowski, Jacek (Czytanie Literatury. Łódzkie Studia Literaturoznawcze, 2012)
In response to the questionnaire, Jacek Brzozowski points to his constant literary fascinations and emphasizes the value of repeated reading and reading comprehension of works which shaped him as a scholar and a man.